Abdominal wall reconstruction using a non-cross-linked porcine dermal scaffold: a follow-up study - Diaz-Siso, J R; Bueno, E M; Pomahač, Bohdan (Hernia, 2013)
PURPOSE: In a previous study, we have shown that non-cross-linked porcine dermal scaffolds (NCPDS) are a safe and effective alternative to prosthetic mesh in the reconstruction of complicated abdominal wall defects. Here, we report the long-term outcomes of abdominal wall reconstruction using NCPDS in a larger patient population. METHODS: Patients who underwent abdominal wall reconstruction with NCPDS between May 2006 and December 2010 were retrospectively reviewed. Analysis of demographics, indications for NCPDS placement, surgical technique, complications, and follow-up data was performed. RESULTS: NCPDS was used for abdominal wall repair in 40 patients. In all patients, NCPDS was positioned using an intraperitoneal technique. At a mean follow-up time of 40.1 months, most patients had successful outcomes. Complications included seroma (21 %), recurrence (7.9 %), and infection (5.2 %); these rates are comparable to our initial report. Two patients died from multi-organ failure unrelated to NCPDS placement. CONCLUSIONS: This study shows that complex abdominal wall defects can be successfully reconstructed using NCPDS with a low rate of recurrence and complications.
Keywords: dospělí; tkáňové podpůrné struktury; Recurrence; Female; ventrální hernie; Adult; ženské pohlaví; mladý dospělý; Adolescent; Hernia, Ventral; Time Factors; časové faktory; lidé; Bioprosthesis; recidiva; bioprotézy; Aged, 80 and over; následné studie; infekce chirurgické rány; Herniorrhaphy; retrospektivní studie; Surgical Wound Infection; Follow-Up Studies; Male; operace kýly; Aged; Young Adult; Abdominoplasty; abdominoplastika; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; serom; Tissue Scaffolds; Retrospective Studies; Seroma; Middle Aged; mladiství; Humans